An investigation of customer satisfaction and loyalty in projects of mini-hotels - Левыкин, Виктор Макарович; Дэвон, Валерия Викторовна (Technology audit and production reserves, 2015)
The hospitality industry continues to evolve and improve in terms of Ukrainian realities of political and economic instability; managers of mini-hotels are experiencing difficulties with the implementation of repeat sales, increasing the number of loyal customers and the preservation of loyal customers, maintaining a high level of consumer loyalty and customer satisfaction. The article reveals the concept of satisfaction and loyalty of mini-hotels customers. It is schematically represented the short-cat and expanded chains of relations needs of consumers and profits of mini-hotels. It is answered the questions about the relationship between the loss of quality of hotel services, customer perceived value, activation of the quality of hotel services and customer satisfaction, as well as consumer loyalty in the hotel industry. The approaches of recovery and improve the quality of hotel services for customer satisfaction are described. Marketing 4P conception was expanded to formula 9P. It is formulated the propositions of "customer satisfaction" and "The Golden Rules of Success." The obtained data indicate that activation of the quality of hotel services has a positive impact on customer loyalty, while the perceived value and customer satisfaction are two essential variables indirectly related to the quality of hotel services and customer loyalty. Article will be relevant for managers of mini-hotels and help them in achieving and maintaining a high level of quality of hotel services, holding regular customers to gain a competitive advantage and increase the market share. The conclusions of the discussion of the investigation results can be used by hoteliers to improve the management of customer satisfaction and loyalty.